Kurangnya Kesadaran Mahasiswa dalam Membuang Sampah Pada Tempatnya di Lingkungan Kampus - Muhamad Hilal Ramadhan; Siti Halimatussa’diah; Reza Mauldy Raharja (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The aim of this research is to determine students' awareness of the importance of disposing of rubbish in the right place, which is an important part of maintaining a clean campus environment. However, this lack of awareness often becomes a detrimental problem, reflecting a lack of understanding of the negative impacts of this behavior. Several factors that may influence this lack of awareness include a lack of environmental education, ignorance of environmental impacts, and a lack of enforcement of regulations related to waste management. The importance of improving student awareness in this regard cannot be overstated, considering their important role in maintaining the cleanliness and sustainability of the campus environment. Therefore, coordinated efforts are needed between educational institutions, local governments and the community to increase students' awareness of the importance of disposing of waste in the right place through education, social campaigns and consistent enforcement of rules. In this way, it is hoped that a clean, healthy and sustainable campus environment can be created for the entire academic community.